Pengaruh Keahlian Audit dan Independensi terhadap Pendapat Audit: Sebuah Kuasieksperimen - Sekar Mayangsari (The Indonesian Journal of Accounting Research, 2013)
Auditor’s opinion is the service product of public accounting firms. Auditor opinion forms the quality assurance of financial statements issued by a corporation. This opinion is based on the auditor’s belief toward the evidence collected. It means that auditor opinion is the auditor’s inference on the evidence collected.  This inference is often incorrect.An opinion on audited financial statement is based on the assumption that the company will be viable during a reasonable period of time (one year, SPAP 341). This going concern concept is the main assumption in publishing a financial statement. Auditors have often made mistakes in predicting a company’s going-concern. Erroneous opinions  occurred not only in Indonesia. Taffler and Citroen (1988) showed that among USA and British companies that failed, only 20 per cent that receive qualified opinion.Actually, the mistakes may simply occur due to fraudulence. But should the frauds were considered nonexistent, the question is, “Why is it happen?” This study tried to answer that question. The results showed that some of these mistakes were due to auditing competence and independence factors (Barnes and Huan 1993; Lee, Tom, and Stone  1995).In addition to auditing skills and independence factors, the decision over the going-concern of a company was a type of decision that needed a testing of a long-term memory (Birenberg and Shields 1984; Libby  1989). A bias may occur because of the error in recalling  other related types of information. This bias will cause the error in drawing a conclusion (Libby 1989). Choo and Trotman (1991) argued that the experienced auditors had more tendencies to recall atypical than typical information.This study was performed using quasi-experiment. The experiment was performed in two stages. In the first stage, an instrument classifying the expert and non-expert and the independent and non-independent was developed.  The instrument was used to manipulate the subjects as the experts and non-experts as well as independent and non-independent. The experimental group was assigned to predict continuity a company in one year later. In the second step, the experiment was per formed to test whether there were treatment differences (expert and non-expert) with respect to the typical and atypical information.The analysis used in the experiment was ANOVA. The results showed that the  opinion on the company going concern of the expert and the independent auditor was statistically different from that of the other experimental group. This finding supported the first hypothesis. Further testing on the impact of expert and nonexpert on the quantity of information use was also determined by the information typed. This was demonstrated by the interaction between the expertise and the type of information. The study results  confirmed Choo and Trotman’s study (1991) that the expert auditors gave more attention to atypical information.